Implementing Strategic Management in Crisis Situations at Luxury Hotel Chain - Okky Friesatama; I Ketut Budarma; Ida Ayu Kade Werdika Damayanti; Ni Wayan Wahyu Astuti; Ni Putu Lianda Ayu Puspita (Catuspata Press, 2022)
Purpose: This paper aims to describe the fact that how a crisis is managed by implementing the right strategic management in the luxury hotel chain. Research methods: The author in this qualitative method conducted interviews with executive members, owner representatives, and heads of departments who are in the organizational structure of crisis management at the hotel. Findings: The hotel chain head office is very concerned about the credibility aspect of its product; scattered hotels are required to follow all standard operating procedures in overcoming crisis situations. The head office requires hotel owners to have insurance in accordance with international standard criteria which are bound in the agreement of both parties. All employees who are in the crisis management organizational structure are to attend training organized by the head office. The head office requires the hotel to work with local agencies to assist with issues and manage communication crises if they occur. Implication: A structured collaboration synergizing between the head office, hotels, local agencies, and hotel owners in managing the crisis that occurs will result in minimizing material and non-material losses.